POLÍTICAS INSTITUCIONAIS CONTRA O ASSÉDIO EM UNIVERSIDADES PÚBLICAS ESTADUAIS BRASILEIRAS - Rossignolli, Bruna Maria (2021)
Harassment events have been visible in Brazilian public opinion in recent years, based on complaints involving different professions, private and public companies, and higher education institutions. This research had sought to understand how Brazilian public state universities have been discussing, reflecting, and coping with harassment. The objective was mapping public state universities’ policies against harassment, investigating their actions. I analyzed institutional documents, and universitary legal production from current 42 public state universities in Brazil. Institutional documents were compared with academic production that discusses harassment, and gender violence. The mapping demonstrates that there is a need to build specific sectors in universities to accommodate victims of harassment.